Kejadian Prehipertensi Pada Siswa SMA di Minahasa Selatan - Wantania, Frans; Rotty, Linda (JKK (Jurnal Kedokteran Klinik), 2019)
AbstractBackground: Subject with prehypertension is in higher risk to have cardiovascular event in the future. Moreover, that it is accompanied with other risk factors such as obesity, smoking, or diabetes mellitus, This research is aimed to look for the correlation between physical activity with the incidence of prehypertension in senior high school on South Minahasa region. Method: This study was held in one of the senior high school in South Minahasa region. Blood pressure, weight measurement and abdominal circumference was examined. Physical activity measurement was based on questionnaire. Definition of prehypertension based on JNC7 criteria is systolic blood pressure more than 120mmHg but less than 140 mmHg, with the diastolic pressure within 80-90mmHg. Furthermore, statistical analysis was done using SPSS computer program to determine the correlation between physical activity and incidence of hypertension. Result: Prehypertension incidence and hypertension in this study was 26% which male student were found more than female student.: ConclusionPrehypertension and hypertension incidence amongst senior high school in South Minahasa were quite high (26%)Key word: Prehypertension, senior high school student AbstrakLatar Belakang: Subyek dengan prehipertensi lebih beresiko mengalami kejadian kardiovaskular di masa mendatang.  Apalagi bila disertai dengan faktor resiko lainnya seperti obesitas,  merokok, atau DM.  Penelitian ini bertujuan untuk melihat hubungan antara aktivitas fisik dengan kejadian prehipertensi pada pelajar SMA di Kabupaten Minahasa Selatan. Metodologi: Penelitian ini dilakukan di salah satu SMA di Kabupaten Minahasa Selatan. Dilakukan pemeriksaan tekanan darah, berat badan, dan lingkar perut.  Penentuan aktivitas fisik subyek ditetapkan berdasarkan hasil pengisisian kuesioner.  Definisi prehipertensi berdasarkan kriteria dari JNC 7 yaitu tekanan darah sistolik lebih dari 120 mmHg tapi kurang dari 140 mmHg, dan atau tekanan darah diastolik lebih dari 80 mmHg tapi kurang dari 90 mmHg.  Selanjutya dilakukan uji statistik menggunakan program komputer SPSS untuk melihat hubungan antara aktivitas fisik dengan kejadian prehipertensi. Hasil: Kejadian prehipertensi dan hipertensi pada penelitian ini sebanyak 26% dimana Siswa pria lebih banyak dari mahasiswa wanita. Kesimpulan: Kejadian prehipertensi dan hipertensi pada siswa SMA di Kabupaten Minahasa Selatan cukup tinggi (26%). Kata Kunci: Prehipertensi, Siswa SMA